Me PENGARUH LAYANAN KONSELING KELOMPOK DENGAN STRATEGI SELF-MANAGEMENT UNTUK MENINGKATKAN KEDISIPLINAN BELAJAR PESERTA DIDIK KELAS XI IPS 2 SMA NEGERI 9 BENGKULU UTARA: Abstrak, Pendahuluan, Metode Penelitian, Hasil Penelitian dan Pembahasan, Kesimpulan, Saran, Daftar Pustaka - Ivan Julianto; Syahriman; Rita Sinthia (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2024)
ABSTRACT The aim of the research was to find out whether class XI IPS 2 students at SMA Negeri 9 North Bengkulu benefited from group counseling services that encouraged the use of self-management strategies to improve study discipline. This research uses quantitative methodology in an experimental environment. Seven students took part in the study. Data was collected using a questionnaire based on learning discipline. The t-test statistic was used to test the data. T=10.425 and sig (2-tailed) 0.000 (0.000 < 0.005) shows that group counseling services with tactics have a significant effect on students' ability to maintain study discipline. The results showed that average scores on tests measuring study discipline were poor before therapy but improved rapidly afterward. Based on the results of this research, students can take advantage of group counseling services provided by guidance and counseling teachers to improve their ability to manage themselves.